UJI DIURETIK INFUSA DAUN TEH HIJAU (Camellia sinensis L.,)PADA TIKUS PUTIH JANTAN GALUR WISTAR ( Rattus norvegicus ) - Fadista Kurnia Dewi (Universitas Duta Bangsa Surakarta, 2021)
ABSTRACT Green tea leaves are natural materials, contains flavonoids can increase the volume of urine, This study aims to determine the diuretic effect of ethanol extract of green tea leaves in male Swiss mice. This study is an experimental post control group design using in male swiss mice were divided into 5 groups: group I negative control with CMC Na 0,5%, group II positive control with furosemide dose of 3,6mg/KgBB, and group III ethanol extract of green tea leaves dose of 250 mg/gBB, group IV ethanol extract of green tea leaves dose of 500 mg/gBB, group V ethanol extract of green tea leaves dose of 750 mg/gBB. Before treatment all mice were given warm water orally, then give it according to the group. Tests on the diuretic effect is done by measuring the urine volume, the measurements of to be conducted every 60 minutes for 6 hours. Data analysis was performed using SPSS 23 with One-way ANOVA test and continue LSD. Results of the average cumulative urine volume group I of 7,01 ml, group II of 12,98 ml, group III of 9, 13 ml, gruop IV of 12, 57 ml, and gruop V of 12, 81 ml . Furthermore, analysis of data using SPSS. LSD test results showed that the group V differ significantly with group II, ie with significant value 0,850 (p> 0.05). Based on the average volume and SPSS can be concluded that the ethanol extract of green tea leaves have a diuretic. Keywords: Diuretics, Infusa Green Tea Leaves, Green Tea Leave